Government Support in Times of Crisis: Transfers and the Road to Socialism - Felipe González; Mounu Prem (Institute of Labor Economics (IZA), 2025)
Despite the adverse effects of economic crises, incumbents often retain significant electoral support. We attribute this resilience to the intensified political returns of transfers during crises. Our context is the largest infant nutrition program in the world, implemented by Salvador Allende and his left-wing coalition in Chile (1970-1973) as part of a large increase in spending that contributed to hyperinflation, scarcity of basic goods, and plummeting real wages. Using administrative data and surveys, we find that the delivery of three cups of milk per day to all preschoolers in the country lowered infant mortality and helped the left-wing government to remain electorally popular. We support the causal interpretation of results by exploiting a family planning program from the late 1960s, information campaigns targeting women, and voting in gender-segregated booths. Furthermore, novel measures of the local severity of the economic crisis reveal that transfers yielded greater political returns in areas hardest hit by economic hardship. Why did the crisis fail to translate into support for the opposition coalition? Survey evidence suggests that transfers swayed voters who perceived the crisis as unrelated to government policies. Overall, our findings demonstrate how direct transfers and heterogeneous perceptions of economic crises can sustain the electoral popularity of governments.
Keywords: H51; N35; N46; P35; 330; government support; transfers; crisis; hyperinflation; socialism